1999
DOI: 10.1017/s0012162299001395
|View full text |Cite
|
Sign up to set email alerts
|

High- or low-technology measurements of energy expenditure in clinical gait analysis?

Abstract: The repeatability of energy-expenditure measurements were studied in five children and four adults without disabilities using the Cosmed K4 (high technology). The ability to detect change in measurements was compared between this instrument and the Physiological Cost Index (PCI; low technology). The results of repeatability (95% range) for oxygen cost were 13.1% in children and 13% in adults. In contrast, the SD of PCI was 6 to 72% of the mean in adults and wider in children (91%; 95% range). The validity of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(44 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…Another study concluded that PCI reproducibility and its relationship tȯ VO 2 were only moderate [24] in children with CP. The validity of PCI as an outcome measure was also questioned by Boyd et al [25] after a study in children and adults with physical disabilities. Keefer et al [26] also re-evaluated the use of HR per walking speed for a group of hemiplegic children and found low correlations between this index and absolute and netVO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that PCI reproducibility and its relationship tȯ VO 2 were only moderate [24] in children with CP. The validity of PCI as an outcome measure was also questioned by Boyd et al [25] after a study in children and adults with physical disabilities. Keefer et al [26] also re-evaluated the use of HR per walking speed for a group of hemiplegic children and found low correlations between this index and absolute and netVO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Because brain lesions and formation abnormalities in children with CP can alter many of these variables and neurodevelopmental therapy emphasizes improvement of all of these variables, the measurement ofVO 2 and EC can indicate subtle changes following neurodevelopmental therapy. The use of EC measurements has increased over the past decade in the assessment of rehabilitation intervention [19][20][21]. However, frequently an index derived from heart rate and walking velocity is still used because of the difficulty of treadmill testing in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Walking velocity and the 6-minute walk are valid and reliable measures of walking ability in children with or without neuromuscular disability. 10,11 TRAINING PROTOCOL Participants were fitted in a harness suspended from a hydraulic weight-support system (LiteGait I system; Mobility Research, AZ, USA) and positioned over a motor-driven treadmill with variable speed control. The 12-session training protocol occurred twice daily (one morning, one afternoon session), 6 days a week for 2 consecutive weeks.…”
Section: Clinical Assessmentmentioning
confidence: 99%